Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1074/jbc.m113.508382
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Positively Charged Residues for Ligand Activation of the GPR35 Receptor

Abstract: Background:The structure and function of GPR35 are not understood. Results: Using a GPR35 activated state molecular model, we identified crucial amino acid residues required for ligand activation using ␤-arrestin trafficking, ERK1/2 activation, and calcium imaging. Conclusion: Arginines in TMH3-4-5-6 affected agonist signaling. Significance: Identification of residues for GPR35 agonist signaling is critical for the design of ligands with improved potency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…For example, indoxyl sulfate, kynurenine and kynurenate signal via the aryl hydrocarbon receptor (AHR) 52 54 , which is expressed in most tissues, including those affected in uremia such as the liver, intestine and kidney 55 , 56 . Kynurenate can also activate the orphan G-couple protein receptor, GPR35 57 , which is largely expressed in tissues affected in uremia, such as the gut and CNS 58 , 59 . CMPF, on the other hand, has been implicated in a glucose sensing mechanism involving OAT3, which is expressed in the pancreas (among other non-renal tissues), leading to altered metabolism 32 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, indoxyl sulfate, kynurenine and kynurenate signal via the aryl hydrocarbon receptor (AHR) 52 54 , which is expressed in most tissues, including those affected in uremia such as the liver, intestine and kidney 55 , 56 . Kynurenate can also activate the orphan G-couple protein receptor, GPR35 57 , which is largely expressed in tissues affected in uremia, such as the gut and CNS 58 , 59 . CMPF, on the other hand, has been implicated in a glucose sensing mechanism involving OAT3, which is expressed in the pancreas (among other non-renal tissues), leading to altered metabolism 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Zhao et al (2014) have reported the results of human GPR35/CXCR8 mutation and computational studies. Homology models of human WT GPR35/CXCR8 in an inactive (R) and active (R*) state were constructed, as well as an R* model of R6.58(240)A GPR35/CXCR8.…”
Section: Gpr35/cxcr8 Structure and Modelingmentioning
confidence: 99%
“…Receptor homology modeling efforts based on the protease-activated receptor 1 structure (the most closely related GPCR to GPR35 for which an atomic level structure is known) indicated that the species-equipotent ligands behaved like human-selective ligands at the human receptor and rat-selective ligands at the rat receptor ( Mackenzie et al, 2014 ), i.e., in order to generate an equipotent response the ligand must bind differently to each ortholog ( Figure 1 ). A number of similar residues were implicated in GPR35 ligand binding in an independent study, in which alanine substitutions were generated at putative ligand-binding residues, and the resulting mutants functionally assessed in a number of distinct assay formats including β-arrestin-2 translocation, extracellular-signal regulated kinase phosphorylation and calcium mobilization ( Zhao et al, 2014 ). In conjunction with receptor homology modeling efforts based on the β 2 -adrenoceptor, arginine residues at positions 4.60, 164, 167, and 6.58 were found to be involved in the binding and/or function of zaprinast and pamoic acid at human GPR35 ( Zhao et al, 2014 ).…”
Section: Receptor Homology Modeling Efforts Indicate That the Bindingmentioning
confidence: 99%
“…A number of similar residues were implicated in GPR35 ligand binding in an independent study, in which alanine substitutions were generated at putative ligand-binding residues, and the resulting mutants functionally assessed in a number of distinct assay formats including β-arrestin-2 translocation, extracellular-signal regulated kinase phosphorylation and calcium mobilization ( Zhao et al, 2014 ). In conjunction with receptor homology modeling efforts based on the β 2 -adrenoceptor, arginine residues at positions 4.60, 164, 167, and 6.58 were found to be involved in the binding and/or function of zaprinast and pamoic acid at human GPR35 ( Zhao et al, 2014 ).…”
Section: Receptor Homology Modeling Efforts Indicate That the Bindingmentioning
confidence: 99%